Risk assessment of metal exposure from nuts consumption in Iran using inductively coupled plasma optical emission spectroscopy (ICP-OES) - Zahra Hadian; Nabi Shariatifar; Majid Arabameri; Mojtaba Moazzen; Amin Mousavi Khaneghah (Journal of Agriculture and Food Research)
In the current study, concentrations of 35 toxic, non-toxic, and essential metals (As, Al, Au, Ba, B, Bi, Be, Cd, Ca, Cr, Cu, Co, K, Fe, Li, La, Mn, Mg, Na, Mo, P, Ni, Pd, Pb, S, Pt, Se, Sb, Sn, Si, Ti, Sr, W, V and Zn) in four different types of nuts (almond, cashew, peanuts and walnut) were assessed using inductively coupled plasma optical emission spectroscopy (ICP-OES). Results showed that the highest average levels of the essential metals in the samples were associated with K (6949.52 ± 1304.73 mg kg−1). Moreover, the samples did not detect Be, Pd, V, Pt, and La. The highest and the lowest average levels of toxic elements belonged to Ba (3.40 ± 2.00 mg kg−1) and Cd (0.02 ± 0.01 mg/kg), respectively. Pb was not detected (< LOD) in these samples. In the selected nut samples, the concentrations of the elements were less than the standards. Principal component analysis (PCA) represented distinguishing patterns based on the elemental composition of nut samples. Estimated daily intake (EDI), incremental lifetime cancer risk (ILCR), and target hazard quotient (THQ) were estimated to assess attributable risks from the elemental analysis using a probabilistic approach based on Monte Carlo simulation (MCS). The PCA visualized five distinguished clusters based on the elemental composition of the nut samples. Generally, the estimated daily intake (EDI) of metals from the selected nuts was less than the recommended dietary allowance (RDA). Risk assessments revealed that the cumulative EDI, THQ, and ILCR for the toxic metals did not include serious risks to human health (THQ ≤1, ILCR ≤10−6) in the scenarios (average exposure and reasonable maximum exposure). Thus, consumption of these nuts appeared to be safe based on the available data. The present findings provide additional information for further studies in food safety.